Addressing CAUTIs with an External Female Catheter. Issue 1 (January 2023) - Tran, Christine; Rodrigue, Debra; Jones, Tasina; Bell, Natalie
ABSTRACT: Background: Catheter-associated urinary tract infections (CAUTIs) can lead to complications that prolong hospital stays and result in patient discomfort as well as increased health care costs and mortality. At our academic medical center in New York City, in 2016-17, 21 of 87 CAUTI cases (24%) were in bedbound female patients in whom indwelling catheters were used for incontinence. Although condom catheters were available as an alternative to indwelling urinary catheters for male patients, there was a lack of effective products for female patients. Methods: A team of clinical nurse specialists (CNSs) conducted a literature search, reviewed internal data on CAUTI rates and catheter use, and searched for available catheter alternatives that would meet the needs of bedbound female patients. The team identified two different external female urinary catheters and piloted both with a focus on efficacy as well as stakeholder satisfaction. Results: In 2019-20, external female catheters were used in 1, 195 unique patients. Approximately 90% of external female catheter use was to avoid using an indwelling urinary catheter. With a cost avoidance of $13, 786 per patient, $16, 473, 912 in costs to the organization were avoided. CAUTI rates in bedbound female patients decreased after implementation of the external female catheters. Conclusion: This initiative demonstrates that external female urinary catheters can be used at other hospitals to decrease indwelling urinary catheter use and CAUTI rates in bedbound female patients. Abstract : After identifying catheter-associated urinary tract infections in bedbound female patients, a team of clinical nurse specialists initiated an intervention using external female catheters to achieve better outcomes, at a significantly lower cost.